?2-macroglobulin function of thioester-containing proteins guards Drosophila from a bacterial protease via two immune-induced peptides. - Cai, C.; Acker, A.; Huang, J.; Liu, Y.; Molino, M.V.; Mariscotti, J.F.; Garcia-Véscovi, E.; Bulet, P.; Hammann, P.; Chicher, J.; Liegeois, S.; Li, Z.; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2026)
RNAseq analysis of the Drosophila genome has revealed further immune-induced genes. Two genes initially annotated as lncRNAs, CG44404(yulü) and CG45045(shenshu), are strongly induced. We report here that these two genes actually encode highly related secreted peptides found in the Sophophora subgenus of Drosophila species. We have generated single and double null mutants of these loci and found that the double mutant line did not display any enhanced susceptibility to an immune challenge with a panel of bacterial and fungal pathogens, except for Pseudomonas aeruginosa. We did not observe any increased P. aeruginosa burden in yulü-shenshu mutants, suggesting that the two peptides may not be required for resistance to infection. Rather, we find that they provide a level of protection against Outer Membrane Vesicles (OMVs) purified from either P. aeruginosa or Serratia marcescens culture supernatants. We have recently reported that S. marcescens OMVs induce the paralysis of flies through the induction of apoptosis in at least some neurons. Much of the virulence of these OMVs is mediated by the metalloprotease PrtA. While Yulü/Shenshu do not display any protease inhibition activity, the detection of an association between Yulü and the Drosophila complement thioester-containing protein 2 (Tep2) led to the finding that both Tep2 and Tep4 mutants are sensitive to the injection of PrtA while their overexpression significantly protects wild-type flies from the effects of this protease. Both Tep2 and Tep4 are able to inhibit the activity of PrtA in a thioester- and yulü/shenshu-dependent manner. Thus, these Teps may also function as ?2-macroglobulins.